Ballistic impact on bi-layer alumina/aluminium armor : a semi-analytical approach - Chi, Runqiang (2013)
This paper presents a semi-analytical approach on the performance of ceramic/metal armor under ballistic impact. Numerical simulations for alumina/aluminum armor impacted by 20 mm APDS in AUTODYN were carried out and verified against the experimental data. Comprehensive numerical simulations were performed using the verified numerical model material parameters providing corroborative data for ensuing discussions. A semi-analytical model relating projectile residual velocity, impact velocity and armor ballistic limit velocity (BLV) is presented for impact of hard projectile against ceramic/metal armor. It is shown that the projectile residual velocity and BLV satisfy the replica scaling laws. Based on the replica scaling laws of projectile residual velocity and BLV, an empirical equation for BLV is obtained and used for armor optimization applications giving reasonable results similar to experiments available in the literature.